How depression impacts on road traffic accidents among older adults and elderly Indians: Evidence from large scale nationally representative survey - Pritam Halder; Immanuel Joshua; Sayan Saha; Abhinav C. S. Kolachala; Risha Gupta; Anshul Mamgai; Sukhmeen Kaur; Ankita Chattopadhyay; Saumyarup Pal; Sayani Bisoi; Shivani Rathor (Journal of Family Medicine and Primary Care)
Introduction: With increased urbanization the prevalence of important public health problems like road traffic accidents (RTA) and depression are surging. This study was aimed to determine the association between RTA and depression among Indian population aged ≥45 years. Methods: Using Longitudinal Aging Study in India (LASI) dataset (April 2017–December 2018), we have conducted this study among older adults (45–59 years) and elderly (≥60 years) Indians. Bivariate analysis was conducted to estimate the prevalence of RTA and depression nationally and across aspirants, achievers, and front runner states. Multivariable logistic regression was conducted between RTA and depression, adjusted with demographic and socioeconomic; health related and behavioral factors. P value <0.05 was considered as statistically significant. Results: Prevalence of RTA was 1.84 (1.74-1.94)% nationally, highest among achiever states (2.04 (1.82–2.30)%). Prevalence of depression was 6.08 (5.90–6.26)% nationally, highest among aspirant states (7.02 (6.74–7.30)%). The adjusted odds of having accident was significantly 1.75 times higher among depressed (aOR 1.75, 95% CI 1.44–2.13) than non-depressed participants which was highest across front runners (aOR 1.86, 95%CI 1.26–2.72) followed by aspirant states (aOR 1.79, 95%CI 1.37–2.33). Conclusion: This study established the association between depression and road traffic accidents among older adults and elderly. Therefore, efforts must be taken to address mental health issues specially focusing on depression in them with proper policy implication more focused on front runners followed by aspirant states.